Antimicrobial activity, phenolic profile and role in the inflammation of propolis - Silva, João (2014)
Nowadays a great amount of information regarding chemical and biological aspects of bee products is available in the literature, but few data on its therapeutic uses are found. The aim of this study was to evaluate the phenolic profile, the in vitro antimicrobial activity and effect in the hyaluronidase enzyme (widely related with the inflammation process) of propolis harvested in Portugal. The efficacy of three extracts (hydro-alcoholic, methanolic and aqueous) was also compared. It was chosen the hydroalcoholic extract, because this was the most effective for extracting phenolic compounds. The antimicrobial activity was accessed in Gram-positive and Gram-negative bacteria and yeasts, isolated from different biological fluids and the results were then compared with the obtained for reference microorganisms. The propolis from Bragança was the one that possessed the highest polyphenols’ content. The sample from Beja showed the less significant inhibition of the hyaluronidase enzyme. Concerning the antimicrobial activity, Candida albicans was the most resistant and Staphylococcus aureus the most sensitive. The reference microorganisms were more sensitive than the ones isolated from biological fluids.